Age - related behaviour on individually caged rabbits - KATSAROU (Α. ΚΑΤΣΑΡΟΥ), A.; TSIRONI (Α. ΤΣΙΡΩΝΗ), A.; SERAFETINIDOU (Μ. ΣΕΡΑΦΕΤΙΝΙΔΟΥ), M.; VOYAZAKI (Χ. ΒΟΓΙΑΤΖΑΚΗ), C.; BAUMANS, V.; KOSTOMITSOPOULOS (Ν. ΚΩΣΤΟΜΙΤΣΟΠΟΥΛΟΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Housing conditions and environmental enrichment of individually caged laboratory rabbits is of great importance for the welfare of the animals and the quality of the experimental results. In order to improve the design of existing environmental enrichment programs for laboratory rabbits, considerable knowledge of the behavioural needs of this species is necessary. Taking this into consideration, the aim of this study was to monitor and analyze the behaviour of juvenile and young adult rabbits in order to establish whether there are any age-dependent differences in grooming, rearing, sniffing, eating, drinking and gnawing. 12 NZW rabbits were divided into two groups: group A consisted of six 6-month-old rabbits (young adults) and group Β consisted of six 2-month-old rabbits (juvenile). All animals were already housed for more than twenty days under the same conditions in the animal facility. Both groups of rabbits were video-recorded between 06:00h - 18:00h for four consecutive days. The frequency of each behaviour was determined and compared in the two groups of rabbits from the video recordings. The frequencies of grooming, eating and gnawing in the young rabbits were significantly greater than those in the older rabbits (p<0.05). No statistical differences were found between the two groups for rearing, sniffing and drinking. From these results, we concluded that even small age differences should be taken into account when designing an environmental enrichment program for individually caged rabbits.